Cells Persistently Infected with Newcastle Disease Virus III. Thermal Stability of Hemagglutinin and Neuraminidase of a Mutant Isolated from Persistently Infected L Cells - Thacore, Harshad R. (1971)
Data were obtained which indicated the possible cause of the defective elution from erythrocytes of the mutant virus (NDV(pi)) isolated from L cells persistently infected with the Herts strain of Newcastle disease virus (NDV(o)). The chicken erythrocyte receptors for the mutant and wild-type viruses were equally sensitive to the action of Vibrio cholera filtrate neuraminidase; this suggests that the failure of NDV(pi) to elute from chicken erythrocytes is not due to a specific neuraminidase-resistant receptor for this virus on the erythrocyte membrane. There was no difference in the enzyme content of the intact virions of NDV(o) and NDV(pi) when tested with a soluble substrate, indicating that the inefficient elution of NDV(pi) was not due to a reduced enzyme content. The neuraminidase activity of intact NDV(pi) virions was significantly more stable at 55 C than the enzyme of NDV(o) virions, whereas the dissociated enzymes of the two viruses were inactivated at the same rate. On the basis of these findings, it seems likely there is a structural difference between the two viruses. The neuraminidase protein of the mutant NDV(pi) may be incorporated into the viral envelope in such a manner that it is prevented from reacting with the substrate in the erythrocyte membrane, although it can react with a soluble substrate. The hemagglutinin activity of both intact and disrupted NDV(pi) was significantly more resistant to thermal inactivation than that of the wild-type NDV(o). This finding suggests a genetic difference in the hemagglutinin protein of the two viruses.